Antifungal activity test of nanosilver in serum cosmetic preparations - Puspitasari, Putri; Taufikurohmah, Titik (Jurnal Pijar Mipa, 2023)
Serum is one of the cosmetic products that people often use today. Along with the times and technological developments, innovations in serum products are also increasing with the addition of active ingredients. Nanosilver is one of the nanotechnology findings and is known as a good antifungal. In this study, serum products were made with the addition of nanosilver as an antifungal, with variations in the acquisition of 20 ppm nanosilver by 5, 10, and 15%. This study aims to determine the characteristics of nanosilver synthesized using UV-Vis Spectrophotometer and TEM, determine the physical and chemical characteristics of nanosilver serum preparations, and determine the antifungal activity of nanosilver in serum cosmetic preparations. In this study, the synthesis of nanosilver using a chemical reduction method with sodium citrate as a reducing agent and stabilizer. Characterization of nanosilver with UV-Vis Spectrophotometer showed that the synthesized nanosilver was relatively stable, and the results of description with TEM showed that the nanosilver produced was on the nanoscale with an average diameter of 35.075 nm and spherical shape. The physical and chemical characteristics of the serum preparation carried out by organoleptic testing showed that the five samples were homogeneous, non-irritating, and had a pH of 6. Testing of nanosilver antifungal activity was carried out by the DMC (Direct Microscopic Count) method with direct counting techniques under a microscope for eight weeks. Based on the calculation results, from week 0 to week 8, it shows that the serum preparation with the addition of nanosilver can inhibit fungi with the growth of the number of hyphae in F1, F2, F3, F4, F5 respectively 24.25; 22.25; 3.25; 3; and 2.75%.